Multi-omics analysis reveals the interplay between pulmonary microbiome and host in immunocompromised patients with sepsis-induced acute lung injury - Fan Lu; Ting Huang; Ruichang Chen; Haiyan Yin (Microbiology Spectrum)
ABSTRACT The mechanisms behind the high inflammatory state and immunocompromise in severe sepsis remain unclear. While microbiota’s role in immune regulation is known, the impact of pulmonary microbiota on sepsis progression is not fully understood. This study aims to investigate pulmonary microbial characteristics in septic patients and their relationship with host immune-related genes and clinical features. Fifty-four sepsis patients were divided into the immunocompromised host (ICH) group (n = 18) and the control group (n = 36). Bronchoalveolar lavage fluid (BALF) was analyzed using metagenomic next-generation sequencing (mNGS) to assess the pulmonary microbiome, and transcriptomic sequencing evaluated host gene expression. The pulmonary microbiota network in the ICH group showed notable alterations. Symbiotic bacteria like Streptococcus salivarius and Streptococcus oralis were key taxa in the control group. In contrast, opportunistic pathogens such as Campylobacter concisus and Prevotella melaninogenica, typically linked to infections in various body sites, dominated in the ICH group. Transcriptomic analysis revealed differential genes between the two groups. The downregulated differential genes in the ICH group were primarily enriched in pathways related to T-cell activation and the Type I interferon signaling pathway, both crucial for the immune system. Further correlation analysis identified significant associations between certain microbes and host genes, as well as clinical indicators, particularly with species like Campylobacter concisus, Streptococcus salivarius, Streptococcus oralis, and several species of Veillonella. These findings suggest that alterations in the pulmonary microbiome, especially the presence of opportunistic pathogens, may contribute to immune dysregulation in immunocompromised septic patients, warranting further research to explore causal relationships.IMPORTANCERecent research has substantiated the significant role of microbiota in immune regulation, which could influence high inflammatory state and immunocompromise in patients with severe sepsis, as well as provide new opportunities for acute lung injury induced by sepsis diagnosis and treatment. Our study identified some potential critical microbes (Campylobacter concisus and several species of Veillonella), which were correlated with immune-related genes and might be the novel target to regulate immunotherapy in sepsis.